Aspects Regarding the Distinctive Features of Clothing Terms at the Level of Meaning of Idiomatic Expressions - Andronic-Bâclea, Cipriana (Acta Universitatis Danubius. Communicatio, 2024)
In expressing their vision of the world, people relate to the real, i.e. concrete domains of existence. The surrounding world, which includes beings, objects or observable phenomena, becomes a reference point in the formulation of judgments that are general in nature. Clothing plays a major role in people's lives, along with food and shelter, and has both a practical function, as it provides protection for the body, and an aesthetic function, providing clues about the social and material status of the individual, through the quantity and quality of the clothing items owned. Each piece of clothing is individualized through a series of features that contribute to the realization of meaning in idiomatic expressions or achieve the semantic differentiation in the case of synonymous series.